Measuring changes in travel behavior pattern due to COVID-19 in a developing country: A case study of Pakistan - Abdullah, Muhammad; Ali, Nazam; Hussain, Syed Arif; Aslam, Atif Bilal; Javid, Muhammad Ashraf (Transport policy, 2021)
Travel behavior has been affected around the world since the eruption of corona virus disease (COVID-19). Several industries including transportation industry have been hard hit by the pandemic. As the virus is transmitted through close contact with infected people, number of outdoor trips has reduced causing roads and public transport to be less crowded than before. In order to develop transport-related policies for the post COVID-19 world, it is necessary to explore how the pandemic has affected the travel behavior pattern. This study explored the influence of the COVID-19 pandemic on travel pattern and mode preferences in Pakistan using a questionnaire survey. The results showed significant shift in primary traveling purpose from work and studying to shopping during the pandemic. Number of trips performed for non-commuting purposes were also significantly different before and during the pandemic. A significant modal shift from motorbike to non-motorized modes of travel was found for distances less than 5 km. For longer distances, people shifted from public transport to private car. These findings suggest that past policies regarding different modes may be revisited in the post COVID-19 world. The statistical tests performed on the factors affecting mode choices indicated that the respondents put more priority on pandemic-related items such as infection concern, social distance, hand sanitizers' availability, and cleanliness, etc., during the pandemic. The findings of this study will certainly help in shaping up the policies for the post COVID-19 world especially in the developing countries. •Primary purpose of traveling changed from work and studying to shopping during the pandemic.•Significant shift from motorbike to non-motorized modes of travel for short distances (<5 km).•Significant shift from public transport to private car for long distances (>5 km).•More priority is put on the factors associated with the pandemic while choosing a transport mode during the pandemic.